Patrimoine vivant et contributions citoyennes. Penser le patrimoine « devant » l’Anthropocène - Jean-Louis Tornatore (In Situ)
The category of intangible cultural heritage has introduced the idea of living heritage, a notion that is somewhat unsettling for France’s cultural and academic worlds. And this is compounded by a clear tendency which sees heritage activities multiplying and going beyond the competence and control of the institutions which are supposed to organise our relations with the past. In this article I would like to draw some conclusions from these two evolutions. If heritage is now living, will it help us face the major issues of the twenty-first century, often condensed in the notion of the Anthropocene? If heritage has been democratised, is it now part of the dynamics of alternative actions often qualified as citizens’? In other words, after having been seen as a way of tempering the destructive effects of capitalism, can heritage be mobilised in and for anti-capitalist initiatives?